İdarenin gıda güvenliğine ilişkin faaliyetleri - Soylu, Ahmet Cemil (My University, 2022)
Geçmişten günümüze insanların en büyük kaygısı yaşam mücadelesi olmuştur. Yaşam mücadelesi içerisinde gerçekleşen savaş ve kavga gibi olayların en büyük sebebi ise su, toprak gibi gıda kaynaklarının ele geçirilmesi ya da korunmasıdır. İnsanlığın tarihsel yönde gelişimi de avcılıktan toplayıcılığa ve tarım toplumuna geçişi çoğunlukla gıda odaklı gerçekleşmiştir. Bunun yanında teknolojinin gelişimi ile gıda işleme ve depolamasının sağlanması sürekli yeni gıda türlerinin ortaya çıkmasına yol açmıştır. Ayrıca insan haklarının evrensel kurallarla tanınması gıda hakkı, sağlık hakkı, bilgi edinme hakkı ve çevre hakkı gibi birçok hakkın doğmasını ve korunmasını sağlamıştır. Kabul edilen birçok hakkın var olması doğrudan veya dolaylı olarak gıda/ beslenme hakkı ile bağdaştırılmaktadır. Zira gıda/ beslenme hakkı kabul edilmediğinde yaşam hakkı ve sağlık hakkı gibi haklar temelinden etkilenmekte iken, çevre hakkı gibi bir hakkın ihlali ise gıda/ beslenme hakkını etkilemektedir. Gıda/ beslenme hakkının gerçekleşebilmesi ancak gıda güvenliğinin sağlanmasından geçmektedir. Gıda güvenliğini sağlama görevi de temelde Devletin/ idarenin sorumluluğundadır. Geçmişten günümüze insanlığın en büyük gündem maddesi olan gıda hakkı ve gıda güvenliğinin sağlanması hususunda idareler düzenleme, gözetim, denetim ve yaptırım gibi faaliyetlerde bulunmakta, gerçekleştirdiği bu faaliyetler dolayısıyla birtakım sorumluluklar altına girebilmektedir.

From the past to the present, humanity’s greatest concern has been the struggle for survival. The biggest cause of wars and battles is the seizure or protection of resources such as water and land. Humanity’s transition from a hunting society to a gathering and farming society over the course of history was largely food-oriented. In the modern age, advances in technology coupled with the availability of new means of processing and storing food have led to the emergence of new types of food. Moreover, the recognition of human rights through universal rules has ensured the emergence and protection of numerous rights, such as the right to food, the right to health, the right to information, and the right to a healthy environment. The existence of many accepted rights is directly or indirectly linked to the right to food/ nutrition. This is because when the right to food/ nutrition is not accepted, rights such as the right to life and the right to health are affected, while the violation of a right such as the right to a healthy environment affects the right to food/ nutrition. The fulfillment of the right to food/ nutrition, on the other hand, depends on ensuring food safety. Food safety is fundamentally the responsibility of the state/ government. Throughout history, administrations have carried out activities such as regulation, monitoring, inspection, and sanctioning to ensure the right to food and food safety—humanity’s greatest concern—leading them to assume a number of responsibilities on account of these activities.
Keywords: Administrative activities; Besin hukuku ve mevzuatı; Food Law; Food law and legislation; Gıda Güvenliği; Gıda Hakkı; Gıda Hukuku; İdari Faaliyetler Food safety; Kamu hukuku; Public law; Right to food; Turkey; Türkiye